Medial glenohumeral ligament reconstruction for ex-vivo medial glenohumeral luxation in the dog - Ringwood, P. B.; Kerwin, S. C.; Hosgood, G.; Williams, J. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
The range of motion (ROM) and instant centre of motion (ICM) of the isolated glenohumeral joint were determined after experimentally induced medial glenohumeral luxation was repaired with a prosthetic medial glenohumeral ligament (MGHL) and biceps brachii tendon transposition (BTT) in 10 canine cadaver forelimbs. In this ex-vivo model, the BTT altered the ROM and ICM significantly more than MGHL reconstruction.
Keywords: Medial glenohumeral ligament; glenohumeral luxation; biceps brachii tendon transposition; dog